How should antenatal counseling be given to parents in the fetal corpus callosum agenesis? - Hasan Süt; Gülşah Aynaoğlu Yıldız (BMC Pregnancy and Childbirth)
Abstract Background We aimed to review the corpus callosum agenesis (CCA) cases diagnosed and managed in our University to contribute to the literature about this antenatally diagnosed fetal cranial anomaly by revealing the antenatal and postnatal outcomes of CCA. Methods This retrospective and cross-sectional study examined CCA detected in our clinic between 2012 and 2021. Genetic results, accompanying additional anomalies, termination, and perinatal mortality rates were also calculated. Neurodevelopmental outcomes were revealed by investigating motor development, cognitive development, behavioral disorder, speech delay, personal-social backwardness, and epilepsy in cases of isolated CCA and non-isolated CCA in the postnatal period. Results Data from 30 fetuses were evaluated during the study. The number of isolated CCA and non-isolated CCA cases is 11 (37.5%) and 19 (62.5%), respectively, and the number of partial CCA and complete CCA cases is 8 (26%) and 22 (74%), respectively. Among the 30 fetuses, the numbers of live births, chromosomal anomalies, perinatal mortalities, and terminations were found to be 14 (47%), 3 (10%), 3 (10%), and 13 (43%), respectively. Postnatal evaluation was performed in 14 children, and normal neurodevelopmental outcomes were observed in 5 (35.7%). All these children were from the isolated CCA group. Additionally, poor neurodevelopmental outcome was detected in 37.5% of isolated CCA. Conclusion If CCA is detected in the fetus, additional ultrasonographic anomaly and genetic examination should be performed to differentiate isolated CCA from non-isolated CCA. While the termination option can be offered to the family by informing them about poor pregnancy outcomes in non-isolated CCA, counseling in isolated CCA remains contradictory, and more comprehensive prospective studies are needed. Trial registration This study was retrospectively registered and authorized by the local Ethics Committee of Ankara University (clinical trial date 06.06.2024/ number 1391402).